2012
DOI: 10.1007/s00056-012-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Class II, Division 2 malocclusions using a completely customized lingual appliance and the Herbst device

Abstract: Class II, Division 2 malocclusions can be efficiently and reliably treated by a combination of a completely customized lingual appliance and the Herbst device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(115 reference statements)
0
10
0
3
Order By: Relevance
“…von Bremen et al [22] showed a mean proclination of 11.8° and 9.3°, with reduced and total mandibular cast splints Herbst, respectively. Other studies also have shown similar values of incisor proclination, even when combining the Herbst appliance with a lingual fixed appliance [2325]. In this study an acrylic splint Herbst was used because in literature it has been reported to have a better mandibular incisor proclination control [9]; as a matter of fact, mean values of incisor flaring are slightly lower than values founded in literature; yet, they are higher than the ones reported by Valant and Sinclair [9].…”
Section: Discussionmentioning
confidence: 71%
“…von Bremen et al [22] showed a mean proclination of 11.8° and 9.3°, with reduced and total mandibular cast splints Herbst, respectively. Other studies also have shown similar values of incisor proclination, even when combining the Herbst appliance with a lingual fixed appliance [2325]. In this study an acrylic splint Herbst was used because in literature it has been reported to have a better mandibular incisor proclination control [9]; as a matter of fact, mean values of incisor flaring are slightly lower than values founded in literature; yet, they are higher than the ones reported by Valant and Sinclair [9].…”
Section: Discussionmentioning
confidence: 71%
“…Similar findings regarding the lingual literature can be explained by the fact that lingual orthodontic treatment was until now, nearly exclusively used in the treatment of adult patients. Only recently, with the introduction of completely customized lingual appliances (CCLA) has orthodontic treatment for younger patients become increasingly popular [2,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…However, as there has also been an increased use of lingual appliances in more complex treatments in adolscents [17], combination of lingual appliances with a Herbst type functional appliance are a common element of the contemporary orthodontic spectrum of therapy [1820]. Similarly to vestibular Herbst derivatives, the fixation of Herbst telescopes in common lingual appliances (Incognito, 3 M Unitek, TOP-Service für Lingualtechnik, Bad Essen, Germany) is achieved by bands on the lower canines and upper first molars, which are simultaneously provided with a lingual bracket [21].…”
Section: Introductionmentioning
confidence: 99%